2015
DOI: 10.1063/1.4931725
|View full text |Cite
|
Sign up to set email alerts
|

Voltage contrast X-ray photoelectron spectroscopy reveals graphene-substrate interaction in graphene devices fabricated on the C- and Si- faces of SiC

Abstract: A consistent and accurate ab initio parametrization of density functional dispersion correction (DFT-D) for the 94 elements

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…By exposing the dielectric surface to a constant flow of either electrons or X-rays, both positive and negative charging of a dielectric grown on a semiconductor were achieved. The experimentally determined photoemission intensities, including broadening and peak shifts, were modeled by making some basic assumptions regarding semiconductor band bending, potential profile across the oxide, and possible defects states in the film. Cohen and co-workers have extended the application of flood gun charging strategies to a wider class of interfaces using the phrase “chemically resolved electrical measurements” to describe their method. Suzer et al have performed extensive XPS-based measurements on defects and charging effects in oxides and have also recently explored in-plane surface potential variations using XPS imaging on in-plane biased structures. Lastly, Kobayashi et al, have applied a bias across a metal/oxide/semiconductor (MOS) stack using 3 nm Pt films as top electrodes and performed XPS in order to model the oxide defects density based on the evolution of the substrate band bending. In all these studies, however, the determination of the potential profile across an entire stack was never performed.…”
mentioning
confidence: 99%
“…By exposing the dielectric surface to a constant flow of either electrons or X-rays, both positive and negative charging of a dielectric grown on a semiconductor were achieved. The experimentally determined photoemission intensities, including broadening and peak shifts, were modeled by making some basic assumptions regarding semiconductor band bending, potential profile across the oxide, and possible defects states in the film. Cohen and co-workers have extended the application of flood gun charging strategies to a wider class of interfaces using the phrase “chemically resolved electrical measurements” to describe their method. Suzer et al have performed extensive XPS-based measurements on defects and charging effects in oxides and have also recently explored in-plane surface potential variations using XPS imaging on in-plane biased structures. Lastly, Kobayashi et al, have applied a bias across a metal/oxide/semiconductor (MOS) stack using 3 nm Pt films as top electrodes and performed XPS in order to model the oxide defects density based on the evolution of the substrate band bending. In all these studies, however, the determination of the potential profile across an entire stack was never performed.…”
mentioning
confidence: 99%
“…We have demonstrated that employing a DC bias during XPS data collection provides us with stable, steady-state information. 46 49 Furthermore, our research has emphasized the essential role of the AC excitation in examining dynamic evolution of the electrical potentials, as showcased in various of our publications. 50 54 Recently, we also reported on the use of Scanning Electron Microscopy (SEM) to detect similar changes caused by potential-induced intensity variations.…”
Section: Introductionmentioning
confidence: 74%
“…We have demonstrated that employing a DC bias during XPS data collection provides us with stable, steady-state information. Furthermore, our research has emphasized the essential role of the AC excitation in examining dynamic evolution of the electrical potentials, as showcased in various of our publications. Recently, we also reported on the use of Scanning Electron Microscopy (SEM) to detect similar changes caused by potential-induced intensity variations . Notably, these measurements have enabled us to observe the effects of time-resolved polarization and screening of metal electrodes into the liquid electrolyte surfaces over significant distances (centimeters) and extended time periods (hundreds of seconds), offering insightful chemical information.…”
Section: Introductionmentioning
confidence: 77%
“…The S1 component is attributed to one-third of the carbon atoms in the buffer layer covalently bonded to the SiC substrate, and the S2 component results from the other two-thirds of the carbon atoms with the sp 2 conguration in the buffer layer. 23,24 Additionally, a minor contribution at high binding energy is attributable to the presence of C]O, 25,26 which might be formed during the process of graphitization, 25 or related to the sample preparation process during the XPS test.…”
Section: Resultsmentioning
confidence: 99%